An updated checklist of \(Aleiodes\) and \(Heterogamus\) species (Hymenoptera, Braconidae, Rogadinae) in Vietnam, with new records - Dang Long, Khuat; Quynh Mai, Pham; Thi Nhi, Pham; Duc Hiep, Nguyen; Dinh Duong, Tran; Thi Hoa, Dang (Academia Journal of Biology, 2023)
This is the most complete list of Aleiodes species of the subfamily Rogadinae from Vietnam, and of the total seventy five species of this genus reported, sixty three species of the subgenus Aleiodes, five of Arcaleiodes, three of Chelonorhogas, and four species of the genus Heterogamus. There are thirty species newly recorded from the Rogadinae fauna of Vietnam. The information on valid names, the published papers of the first record of Aleiodes species in Vietnam and the distribution of Aleiodes species were also provided. Additionally, there are three species listed with information about their hosts, being agricultural pests controlled to some degree by these parasitoids.